2010
DOI: 10.1007/s00384-010-1051-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of response to preoperative radiotherapy, lymph node metastasis, and CEA level in patients undergoing total mesorectal excision of rectal cancer

Abstract: Pathological lymph node metastasis and a high CEA level after radiotherapy were independent predictors of a poor outcome in rectal cancer patients treated with preoperative radiotherapy. The CEA level after radiotherapy was capable of discriminating patients with a high risk of recurrence among pathologically node-negative patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
0
20
1
Order By: Relevance
“…The micro-RNA signature may be of value in predicting pCR [18], but will need further validation. Several studies had focused on the predictive value of pre- and post-CRT CEA levels in patients with rectal cancer receiving pre-operative CRT [12-15,19,20]. In this study, we found not only pre-CRT CEA levels had prognostic significance, “normalization” of these values and CEA ratio also predicted tumor response and may be helpful in the design of individualized treatment for rectal cancer with high CEA levels before treatment.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The micro-RNA signature may be of value in predicting pCR [18], but will need further validation. Several studies had focused on the predictive value of pre- and post-CRT CEA levels in patients with rectal cancer receiving pre-operative CRT [12-15,19,20]. In this study, we found not only pre-CRT CEA levels had prognostic significance, “normalization” of these values and CEA ratio also predicted tumor response and may be helpful in the design of individualized treatment for rectal cancer with high CEA levels before treatment.…”
Section: Discussionmentioning
confidence: 51%
“…It was reported that pre-CRT CEA levels >2.5 or >5 ng/ml were associated with poor pCR rates and poor disease-free survival on univariate analysis, but not for both on multivariate analysis [12,13]. However, in other studies, pre-CRT CEA levels were a common predictor of downstaging, pCR and tumor response on multivariate analysis [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, in this study, the likelihood of 3-year DFS decreased with increased ypTNM stage. However, the ypTNM stage could roughly classify NCRT-treated patients mainly because the key determination was lymph node involvement, whereas the depth of tumor invasion had less impact on DFS [69]. In addition, patients with pCR had the most favorable outcome, which might overestimate the difference among a large number of patients with residual disease.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the absence of an adequate follow-up but the need for fresh frozen biopsies to perform the genome-wide CpG scan, targets were selected based on tumor regression grading (TRG) and post-therapeutic lymph node status (ypN) after CRT. Both parameters are known to be well-established surrogate parameters for outcome in rectal cancer [15, 4448]. The study was conducted in accordance with the Helsinki Declaration and was approved by the ethics committee of the University Medical Center Goettingen.…”
Section: Methodsmentioning
confidence: 99%